1992
DOI: 10.1029/92jc01001
|View full text |Cite
|
Sign up to set email alerts
|

Formation and spreading of subtropical mode water in the North Pacific

Abstract: A time‐averaged description of the formation and spreading of North Pacific subtropical mode water (NPSTMW) is presented. The formation of NPSTMW is studied using TRANSPAC expendable bathythermograph data. The data are transformed into a stream coordinate system and averaged. The coordinate system uses the position of the Kuroshio front as its origin. Maps are presented of the temperature structure and mixed layer distribution in winter relative to the Kuroshio front. The formation of NPSTMW occurs in two sepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
102
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(109 citation statements)
references
References 25 publications
(22 reference statements)
6
102
0
1
Order By: Relevance
“…This suggests that part of the STMW formed in the upstream KE recirculation gyre can be expected to be advected downstream. Indeed, STMW with similar properties has been observed as far downstream as the date line (e.g., Bingham 1992;Suga et al 1997;Oka and Suga 2003). The synoptic KESS survey in May 2004 also revealed that STMW was more intense and larger in thickness near the center of the recirculation gyre.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…This suggests that part of the STMW formed in the upstream KE recirculation gyre can be expected to be advected downstream. Indeed, STMW with similar properties has been observed as far downstream as the date line (e.g., Bingham 1992;Suga et al 1997;Oka and Suga 2003). The synoptic KESS survey in May 2004 also revealed that STMW was more intense and larger in thickness near the center of the recirculation gyre.…”
Section: Discussionmentioning
confidence: 68%
“…12d that the low-PV signal of the mixed layer is in contact with the underlying STMW from mid-February to early April, it is important to emphasize that these two low-PV waters have different poten- tial densities. 1 Previous studies by Bingham (1992), Huang and Qiu (1994), and Oka and Suga (2003) have noted that STMW formed in the KE recirculation gyre tended to spread south-and southwestward through the process of lateral induction. With the observed T-S properties slightly colder and fresher than those shown in Fig.…”
Section: B South Of the Recirculation Gyrementioning
confidence: 96%
See 1 more Smart Citation
“…In particular, in the western North Pacific between 30-45 • N, mixed layer depths can often exceed 200 m (Ohno et al, 2009;Oka et al, 2007 (Bingham, 1992;Hanawa and Suga, 1995), known to be enriched in Al (Measures et al, 2005), outcrops or forms south of the Kuroshio Extension (generally south of 36 • N, Fig. 1) (Chen, 2008;Oka et al, 2007).…”
Section: Hydrographic Influencesmentioning
confidence: 99%
“…During the northern winter, when cold outbreaks of continental air masses spread eastward over the warm water south of the Kuroshio, large heat losses to the atmosphere result in episodes of oceanic convection, forming NPSTMW (Masuzawa 1969;Suga et al 1989;Bingham 1992;Suga and Hanawa 1995;Hanawa and Suga 1995;Oka and Suga 2003). According to these studies, the water mass forms in a mixed layer deeper than 200 m, and its core layer temperature and salinity range is 16°C to 18.2°C and 34.75 to 34.85 psu, respectively.…”
Section: The Kuroshio Extension System Region and North Pacific Subtrmentioning
confidence: 99%